Efficacy of chimeric antigen receptor T cell therapy and autologous stem cell transplant in relapsed or refractory diffuse large B-cell lymphoma: A systematic review - Tian, Linyan; Li, Cheng; Sun, Juan; Zhai, Yixin; Wang, Jinhuan; Liu, Su; Jiang, Yanan; Wu, Wenqi; Xing, Donghui; Lv, Yangyang; Guo, Jing; Xu, Hong; et al. (Frontiers in Immunology, 2023)
Background: We aimed to compare the efficacy of chimeric antigen receptor T (CAR-T) cell therapy with that of autologous stem cell transplantation (auto-HSCT) in relapsed/refractory diffuse large B cell lymphoma (R/R DLBCL). Research design and methods: We searched eligible publications up to January 31st, 2022, in PubMed, Cochrane Library, Springer, and Scopus. A total of 16 publications with 3484 patients were independently evaluated and analyzed using STATA SE software. Results: Patients who underwent CAR-T cell therapy showed a better overall response rate (ORR) and partial response (PR) than those treated with auto-HSCT (CAR-T vs. auto-HSCT, ORR: 80% vs. 73%, HR:0.90,95%CI:0.76-1.07,P = 0.001; PR: 20% vs. 14%, HR:0.65,95%CI:0.62-0.68,P = 0.034). No significant difference was observed in 6-month overall survival (OS) (CAR-T vs. auto-HSCT, six-month OS: 81% vs. 84%, HR:1.23,95%CI:0.63-2.38, P = 0.299), while auto-HSCT showed a favorable 1 and 2-year OS (CAR-T vs. auto-HSCT, one-year OS: 64% vs. 73%, HR:2.42,95%CI:2.27-2.79, P < 0.001; two-year OS: 54% vs. 68%, HR:1.81,95%CI:1.78-1.97, P < 0.001). Auto-HSCT also had advantages in progression-free survival (PFS) (CAR-T vs. auto-HSCT, six-month PFS: 53% vs. 76%, HR:2.81,95%CI:2.53-3.11,P < 0.001; one-year PFS: 46% vs. 61%, HR:1.84,95%CI:1.72-1.97,P < 0.001; two-year PFS: 42% vs. 54%, HR:1.62,95%CI:1.53-1.71, P < 0.001). Subgroup analysis by age, prior lines of therapy, and ECOG scores was performed to compare the efficacy of both treatment modalities. Conclusion: Although CAR-T cell therapy showed a beneficial ORR, auto-HSCT exhibited a better long-term treatment superiority in R/R DLBCL patients. Survival outcomes were consistent across different subgroups.